Impact Of Networking Capability On Marketing Performance: The Mediating Role Of Customer Orientation In MSMES - Joice Jeremy; Lie Heng; Dewi Santika (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2025)
Developments in technology and information have changed the way companies interact with their customers and business partners. These advances allow companies to build wider and more efficient networks, and collect richer data about customer needs and preferences. This study was conducted to determine the relationship of networking capabilities to marketing performance through customer orientation as mediation. Quantitative research and primary data were obtained from distributing questionnaires. The data processed amounted to 111 respondents from MSMEs in Pontianak City. The sampling technique used purposive sampling which was then processed with the help of SPSS AMOS version 26. The results of this study found a significant mediating role of customer orientation in enhancing the impact of the influence of network capabilities on marketing performance. Networking capabilities and customer orientation are two key factors that can affect the marketing performance of an organization. Both play an important role in building and maintaining strong relationships with customers and in responding effectively to market changes